PENGARUH PENGEMBANGAN KARIR, PELATIHAN, KOMITMEN ORGANISASI DAN KERJA SAMA TIM TERHADAP KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN (DAMKAR) KABUPATEN LABUHANBATU SELATAN - Azhari, Khairi; Halim, Abdul; Meilia, Yona (Jurnal Investasi, 2025)
The Civil Service Police Unit and the Fire Department (Damkar) of South Labuhanbatu Regency are the locations of this quantitative research. All 53 people who became research participants were employees of the Fire Department (Damkar) of South Labuhanbatu Regency, as the name of the department is. In this sampling method, a saturated sampling strategy was used, namely the entire population of less than one hundred people were sampled. The sample size in this study was fifty-three employees. In this study, the data collection techniques used were Likert scale questionnaires, recording, and observation. For the purposes of this study, the traditional assumption test was used. The tests include heteroscedasticity, multicollinearity, and data normality tests. For the purposes of multiple linear regression analysis, the SPSS program was used to simultaneously test the partial (t), simultaneous (F), and coefficient of determination tests. The performance of employees at the Civil Service Police Unit and the Fire Department (Damkar) of South Labuhanbatu Regency was partially and simultaneously influenced by several factors including career development, training, organizational commitment, and cooperation, as explained in the results of this study.